Pemberdayaan Ekonomi Masyarakat melalui Home Industry Kerajinan Anyaman Bambu di Desa Banjarwaru Kecamatan Nusawungu Kabupaten Cilacap - Imronah, Ainul; Fatmawati, Nely (Jeksyah: Islamic Economics Journal, 2021)
The woven bamboo craft is a hereditary heritage from our ancestors who keep artistic concepts purely for beauty. Banjarwaru Village is one of the villages that have the potential to develop woven bamboo crafts in the Nusawungu District. The development of the art of weaving batik has become one of the economic potentials and sources of changing the community’s economy. This research is field research (field research) with qualitative data analysis. The results of the study show that: (1) there are several efforts made in community economic empowerment, namely: human development (conducted by socialization in the form of mentoring and coaching), business development (done by conducting job training), environmental development (counseling on environmental care) and institutional development (providing facilities from agencies and institutions that cooperate with the home industry). (2) The impacts of community economic empowerment positive impacts such the fulfillment of daily needs, reduced unemployment, being able to increase the production of goods for weavers. And the negative impact is the use of dyes that can pollute the environment.